From Dust They Came: Government Camps and the Religion of Reform in New Deal California. By Jonathan H. Ebel. New York: New York University Press, 2023 - Pehl, Matthew (Church history, 2024)
From Dust They Came: Government Camps and the Religion of Reform in New Deal California. By Jonathan H. Ebel. New York: New York University Press, 2023. - Volume 93 Issue 3.